Sports Broadcasting - Solberg Harry Arne; Helland Knut (Nordicom Review, 2011)
The present article analyses how various forms of business integrations, combined with technology innovation, have affected the sports broadcasting market in Norway. Interviews with representatives of Norwegian TV broadcasters and transmission companies documented that extremely fierce competition can motivate former rivals to collaborate. Even the new entrants tend to operate together with others instead of operating autonomously. Such collusion can transfer market power from the sellers to the buyers of sports rights. The interviews showed how product innovations can improve the profitability of sports broadcasting. They confirmed that integration can generate economies of scope advantages (cost reductions from the joint use of inputs), for example by using labour more efficiently within parent companies. Additionally, they also showed that economies of scope advantages can come from similarities in the distribution of goods and services, not only from similarities in the production process.